HUBUNGAN REGULASI EMOSI TERHADAP PENERIMAAN DIRI SISWA KELAS XII DI PONDOK PESANTREN MIFTAHUL HUDA BOGOR - Maghfirah Qonitatunnisa; Putri Ria Angelina; M. Kholil Nawawi (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
both socially and emotionally. However, it was found that some students still experience difficulties in managing their emotions and show low levels of self-acceptance. This study aims to determine the relationship between emotion regulation and self-acceptance among students in this environment. The research uses a quantitative approach with a correlational method. The sample consisted of 65 students selected using a saturated sampling technique. The instruments used were an emotion regulation scale based on Gross's theory and a self-acceptance scale based on Jersild's theory. Based on the data analysis and discussion, it was found that the majority of 12th-grade students at Pondok Pesantren Miftahul Huda Bogor have a moderate level of emotion regulation, as evidenced by 42 respondents (64.6) being in the moderate category. Similarly, the level of self-acceptance among these students was also in the moderate category, with 33 respondents (50.8) falling into that group. Pearson correlation test results showed a positive and significant relationship between emotion regulation and self-acceptance, with a correlation coefficient of r  0.583 and a significance value of 0.001. This means that the higher the students’ ability to regulate their emotions, the higher their level of self-acceptance. Thus, the hypothesis in this study is accepted. This research suggests the need for the development of emotional regulation training programs to support the optimal development of students self-acceptance.